1997
DOI: 10.1093/molehr/3.9.743
|View full text |Cite
|
Sign up to set email alerts
|

RU486 inhibits synthesis of an endogenous inhibitor of cell arachidonate release from choriodecidua tissue

Abstract: Gravidin is a potent phospholipase A2 inhibitor that may contribute to the maintenance of human pregnancy. The aims of this study were to determine firstly, the site of gravidin synthesis within placental membranes and secondly, whether the antiprogestin compound, RU486, regulates synthesis. Membrane explants were taken from placentae, dissected and cultured in the presence of RU486, progesterone or inhibitors of DNA or protein synthesis and gravidin production was measured by a specific enzyme-linked immunoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Monensin is a Na ϩ ionophore that blocks posttranslational processing events that take place in internal cellular compartments without affecting activities at the cell surface (32). Conversely, cycloheximide is an antibiotic that inhibits de novo protein synthesis by blocking translation of RNA (33). We found that during the course of 24-h incubation, sTLR2 accumulated in the explant medium villous tissue.…”
Section: Monensin But Not Cycloheximide Affects the Release Of Stlr2 mentioning
confidence: 85%
See 1 more Smart Citation
“…Monensin is a Na ϩ ionophore that blocks posttranslational processing events that take place in internal cellular compartments without affecting activities at the cell surface (32). Conversely, cycloheximide is an antibiotic that inhibits de novo protein synthesis by blocking translation of RNA (33). We found that during the course of 24-h incubation, sTLR2 accumulated in the explant medium villous tissue.…”
Section: Monensin But Not Cycloheximide Affects the Release Of Stlr2 mentioning
confidence: 85%
“…A flowchart of the women enrolled in the study and subgroups of samples analyzed are presented in the supplemental Fig. 4 Amniotic fluid was retrieved from 109 women who had a clinically indicated amniocentesis in the following different populations: second trimester normal genetic karyotyping (GA median (range), 19 (15)(16)(17)(18)(19)(20)(21)(22)(23) wk, n ϭ 14), third trimester fetal lung maturity testing before cesarean delivery (GA, 37 (35)(36)(37)(38)(39) wk, n ϭ 14), and women admitted with symptoms of preterm labor who had an amniocentesis to rule out infection (GA, 28 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) wk, n ϭ 81). To avoid selection bias, women in this last group were selected from a prospective cohort of 463 consecutive patients enrolled at Yale New Haven Hospital from March 2004 to June 2008.…”
Section: Patient Population and Amniotic Fluid Samplesmentioning
confidence: 99%